Peran Katekese Keluarga Sebagai Persekutuan Umat Beriman di Zaman Sekarang Menurut Dokumen Familiaris Consortio Artikel 51-54 - Wenseslaus Jugan; Heribertus A. Bugis; Charolus G. D. Santos; Yohanes Wilson B. Lena Meo (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
The focus of this research is to delve into and re-understand the apostolic exhortation of Pope John Paul II regarding the document Familiaris Consortio, specifically articles 51-54. This document specifically discusses the role of Christian families in the dynamics of contemporary times. This theme is very intriguing to study because it is relevant to the current family situation. The aim of this research is to make the Familiaris Consortio document a guide to enhance the understanding and awareness of families in carrying out their vocation. As a